An optimum design methodology for planar-type coaxial probes applicable to broad temperature permittivity measurements - Kim, Namgon; Yoon, Jeonghoon; Cho, Sungjoon; Cho, Jeiwon; Cheon, Changyul; Kwon, Youngwoo (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
A planar-type coaxial probe applicable to wide temperature and frequency range has been developed. The probe employs a dielectric with a low coefficient of thermal expansion to minimize the effect of thermal deformation for broad temperature measurements. Additionally, a detailed design methodology has been developed to optimize the probe apertures in an effort to minimize the measurement uncertainty while maximizing the operating bandwidth. For this purpose, thorough sensitivity analysis has been employed to correlate the probe structures and dimensions to the individual sensitivity parameters. The analysis has been validated by parametric experiments. By using the dielectric with a low coefficient of thermal expansion and optimizing the probe dimensions, accurate permittivity measurements have been demonstrated from -30 degrees C to 75 degrees C with 40-GHz bandwidth. With the application of the error-correction method, the measurement temperature range has been further extended all the way up to the boiling temperature of water (similar to 100 degrees C). Furthermore, the complex permittivities of methanol have been measured from -30 degrees C to 50 degrees C and the dispersion parameters and full interpolation formulas have been extracted.
Keywords: DIELECTRIC-PROPERTIES; FREQUENCY PERMITTIVITY; BIOLOGICAL TISSUES; CALIBRATION; LINE; METHANOL; SENSORS; LIQUIDS; WATER